Movimento de acesso aberto no brasil: contribuição do Instituto Brasileiro de Informação em Ciência e Tecnologia a partir da implementação do Sistema Eletrônico de Editoração de Revistas - Bandeira, Pablo Matias (2017)
To analyze the results of the implementation of the Electronic Journaling System (SEER), the Open Journal System customization by the Brazilian Institute of Science and Technology Information (IBICT), as part of a policy of free access to scientific information in Brazil between 2003 (Year of its creation) and 2016. It is proposed to create a context based on the concept of "open access", combining the conceptual threads of "scientific communication", intertwined with "scientific publishing", which in turn is interwoven with " Dissemination of scientific and technological information ", for a qualification of an access policy through the adoption of collaborative and free technology. The study allowed to raise important characteristics of Brazilian scientific journals. Today there are no major challenges in the Open Access Movement: a convergence of interests and needs of the editors of the SEER / OJS journals by cooperation networks; An enlargement without sharing and systematizing the successful experiences of journals with high impact indexes, perhaps the biggest challenge today is the integration of data from electronic journals with institutional repositories. Brazil along with the Cariniana preservation network has made significant progress in this integration.